FRI0493 THE INTERLEUKIN-1B INHIBITOR CANAKINUMAB FOR REFRACTORY STILL'S DISEASE: LONG-TERM EXPERIENCE IN 50 CONSECUTIVE PATIENTS. (2nd June 2020) - Laskari, K.; Athanassiou, P.; Georgiadis, A.; Gerodimos, C.; Gkoni, G.; Daoussis, D.; Dimitroulas, T.; Dimopoulou, D.; Iliou, C.; Kallitsakis, I.; Karamitsos, D.; Katsiari, C.; et al.
Abstract : Background: Interleukin-1 (IL-1) is a major mediator of the inflammatory cascade in Still's disease and an established therapeutic target. Objectives: To assess the efficacy and safety of the IL-1b inhibitor canakinumab in adolescent and adult patients with refractory Still's disease. Methods: We conducted a retrospective longitudinal outcome study of 50 consecutive patients aged 39 years (median, range 14-72), fulfilling the Yamaguchi disease classification criteria, with active disease despite treatment with corticosteroids (CS) (n=11) and/or methotrexate (n=9) and/or biologics (n=30) [tumor necrosis factor inhibitors (n=13), IL-6 blockade (n=7), abatacept (n=2), anakinra (n=24); ≥1 biologics (n=13)]. Canakinumab 150-300 mg was administered sc, starting every 4 (n=48) or 8 weeks (n=2), for a median of 24 months (range 3-84). Concomitant treatment included CS (n=41), methotrexate (n=12) and leflunomide (n=3). Results: Complete remission was initially achieved in 78% of patients within a median time of 3 months, irrespective of age at disease onset. Partial clinical and laboratory response was evident in 20%. Canakinumab was discontinued in one patient with resistant disease (primary failure) and in 6 out of 10 initial responders, who relapsed during treatment (secondary failure). Of 39 patients in complete remission, increase in drug administration interval and/or drug dose reduction was attempted in 7, of which only 1 relapsed, whereas drug discontinuation was attempted in 19 patients for a median time of 8 months (range 3-68), of which 8 relapsed. Overall, in half of all disease flares, canakinumab re-introduction or intensification was successful. Canakinumab had a significant CS sparing effect permitting weaning in 21 of 41 cases. Infections (20%, severe 4%) and leucopenia (6%) led to treatment cessation in one patient. Conclusion: In this largest so far real-life patient cohort with refractory Still's disease, high rates of sustained remission were induced by canakinumab both in adolescent and adult patients. Disclosure of Interests: Katerina Laskari: None declared, Panagiotis Athanassiou Grant/research support from: MSD, Genesis pharma, Janssen, Consultant of: Roche, Genesis pharma, Janssen, Speakers bureau: MSD, Janssen, Roche, Genesis pharma, Athanasios Georgiadis: None declared, Charalampos Gerodimos: None declared, Georgia Gkoni: None declared, Dimitrios Daoussis: None declared, Theodoros Dimitroulas: None declared, Despoina Dimopoulou: None declared, Chrysoula Iliou: None declared, Ioannis Kallitsakis Grant/research support from: MSD, Speakers bureau: Genesis pharma, Bristol-Myers Squibb, Dimitrios Karamitsos: None declared, Christina Katsiari: None declared, Stamatis-Nick Liossis: None declared, Clio Mavragani: None declared, CHARALAMPOS PAPAGORAS: None declared, Dimitrios Pikazis: None declared, Ioannis Raftakis: None declared, Theodosios Sarikoudis: None declared, Loukas Settas: None declared, Prodromos Sidiropoulos: None declared, Despoina Soukera: None declared, Evangelos Theodorou: None declared, Panagiota Tsatsani: None declared, Eleni Tsiakou: None declared, Dimitrios Vassilopoulos: None declared, PANAYIOTIS VLACHOYIANNOPOULOS: None declared, Georgios Vosvotekas: None declared, Paraskevi V. Voulgari: None declared, Marina Zakalka: None declared, Maria Tektonidou Grant/research support from: AbbVie, MSD, Novartis and Pfizer, Consultant of: AbbVie, MSD, Novartis and Pfizer, Petros Sfikakis Grant/research support from: Grant/research support from Abvie, Novartis, MSD, Actelion, Amgen, Pfizer, Janssen Pharmaceutical, UCB